Pretty penny farm - Hoppe, Joanne (New York : Morrow, 1987)
Spending the summer on a New Hamsphire farm, fifteen-year-old Beth trains a beautiful chestnut horse for a local race and develops a friendship with an unpopular classmate.
Keywords: Horses -- Fiction; Horse racing -- Fiction; Friendship -- Fiction; New Hampshire -- Fiction